2015
DOI: 10.17554/j.issn.2410-0579.2015.01.4
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Cancer and Urinary Schistosomiasis in Angola

Abstract: Schistosomiasis haematobia is among the most prevalent parasitosis in Angola. The pathology is characterized by serious and irreversible lesions in the urogenital tract induced by chronic infection with the parasite that can eventually lead to squamous cell carcinoma of the bladder. Considering the frequency and severe morbidity observed, even in younger ages, the purpose of this study was to assess the prevalence and morbidity of S. haematobium infection in Angola. A baseline survey was conducted between Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
3
14
1
Order By: Relevance
“…Chronic inflammatory reactions seem to influence carcinogenesis, as observed in various malignancies. In bladder cancer, the infection with schistosomas is strongly associated with the risk of squamous carcinoma of the bladder, and there seem to be gender-specific differences in the prevalence of schistosoma infection ( 84 ). In addition, other pathogens inducing inflammatory reactions may have an impact on the risk of developing UCB.…”
Section: Female With Bladder Cancer: Why Is There a Difference?mentioning
confidence: 99%
“…Chronic inflammatory reactions seem to influence carcinogenesis, as observed in various malignancies. In bladder cancer, the infection with schistosomas is strongly associated with the risk of squamous carcinoma of the bladder, and there seem to be gender-specific differences in the prevalence of schistosoma infection ( 84 ). In addition, other pathogens inducing inflammatory reactions may have an impact on the risk of developing UCB.…”
Section: Female With Bladder Cancer: Why Is There a Difference?mentioning
confidence: 99%
“…Recently, a retrospective review of 185 patients in north-western Tanzania reported 55.1% of SCC whereas 40.5% TCC and 44.9% of all cancer cases were found to have Schistosoma eggs [8]. Similarly, a study from Angola reported a prevalence of 71.7% S. haematobium infection with 3.4% vesical tumor, classified as SCC [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a prevalence of 71.7% S. haematobium with 44.8% and 10.3% granulomas and calcifications of the bladder wall, respectively, was reported in Angola. The study also revealed about 3.4% vesical tumor classified as squamous cell carcinoma ( 17 ). Schistosoma haematobium has been classified as a class 1 carcinogen by the WHO/IARC ( 18 ) and an enormous body of evidence exists to support that assertion.…”
Section: Introductionmentioning
confidence: 85%